Pulmonary vein isolation using a higher power shorter duration CLOSE protocol with a surround flow ablation catheter. (2nd September 2019) - Berte, Benjamin; Hilfiker, Gabi; Russi, Ian; Moccetti, Federico; Cuculi, Florim; Toggweiler, Stefan; Ruschitzka, Frank; Kobza, Richard
Abstract: Introduction: The CLOSE protocol combines ablation index (AI) and ≤6 mm interlesion distance using standard power settings for the treatment of atrial fibrillation (AF). The purpose was to compare the safety and efficacy of a conventional CLOSE and a higher power shorter duration (HPSD)‐CLOSE pulmonary vein isolation (PVI) strategy. Methods and Results: All consecutive patients referred for PVI were included after informed consent was obtained from them. Group 1 was treated with a standard CLOSE protocol and group 2 with a HPSD‐CLOSE protocol (45 W anterior and 35 W posterior). Procedural parameters and 6‐month follow‐up were analyzed. In total, 174 patients (group 1: n  = 94 [paroxysmal: n  = 74]; group 2: n  = 80 [paroxysmal: n  = 65], similar baseline characteristics) were included. PVI was reached in all, but procedure duration (82 ± 18 minutes vs 100 ± 22 minutes; P  < .0001) and radiofrequency (RF) time (23 ± 5 minutes vs 36 ± 11 minutes; P  < .0001) was shorter in group 2. First pass isolation was similar in groups 2 and 1 (left veins: 94% vs 90%; P  = .42 and right veins: 83% vs 84%; P  = .79, respectively). Six‐month off‐ antiarrhythmic drugs freedom of AF/AT was similar in groups 2 and 1 (82% [paroxysmal: 86%] vs 83% [paroxysmal: 88%]; P  = .93, respectively). Major complications were similar (group 2: 1% vs group 1: 3%; P  = .39). Conclusion: A higher‐power short duration approach can shorten a CLOSE procedure and reduce ablation time without having a negative impact on safety or efficiency.